Women's participation in disaster recovery after the 2005 Kashmir, Pakistan earthquake. Issue 4 (1st August 2022) - Gul, Shehla; McGee, Tara K.
Abstract : This study sought to learn how women participated in the recovery process after the Kashmir earthquake of October 2005 in Union Council Langarpura, Azad Kashmir state of Pakistan. Focus‐group discussions, semi‐structured interviews, and participant observations were conducted with a total of 48 participants. The results revealed that women played various important roles in the reproductive, productive, and community spheres, encompassing, inter alia, normal household responsibilities of cooking, cleaning, and caring for cattle, and non‐traditional tasks such as rebuilding the home. In addition, they participated in income‐generating activities such as carrying construction materials and water for daily wages, dairy farming, and working in fields and in the education and health sectors. Community endeavours, meanwhile, consisted of search and rescue, caring for the injured, collective cooking and food sharing, and supervising the reconstruction of public structures, including schools, roads, and water supply facilities, and establishing a sewing centre to provide vocational training to local women. نبذة مختصرة: هدفت هذه الدراسة إلى التعرف على كيفية مشاركة النساء في عملية التعافي بعد زلزال كشمير في أكتوبر 2005 في مجلس اتحاد لانغاربورا بولاية آزاد كشمير الباكستانية. جرت مناقشات مجموعة التركيز (عددها 2)، والمقابلات شبه المنظمة (عددها 34)، وملاحظات المشاركين بإجمالي بلغ 48 مشاركاً. كشفت النتائج أن النساء في لانغاربورا اضطلعن بمختلف الأدوار المهمة في مجالات الصحة الإنجابية، والإنتاجية، والمجتمعية. تضمنت أدوار النساء واجباتهن المنزلية الاعتيادية المتمثلة في الطهي، والتنظيف، ورعاية الماشية. كما تضمنت مسؤوليات غير تقليدية مثل إعادة بناء منازلهن. كما اضطلعت النساء في لانغاربورا بأدوار إنتاجية تتمثل في المشاركة في الأنشطة المدرة للدخل مثل حمل مواد البناء، والمياه مقابل أجر يومي، والعمل في الحقول، ومزارع الألبان، والعمل في قطاعي التعليم والصحة. من ناحية أخرى، تألفت الأدوار المجتمعية من أنشطة بحث وإنقاذ، ورعاية للمصابين، وطهي جماعي، وتقاسم للطعام، وأدوار غير تقليدية للإشراف على إعادة بناء المباني العامة، بما في ذلك المدارس، والطرق، ومرافق إمدادات المياه، وإنشاء مراكز الخياطة، لتوفير تدريب مهني للمرأة المحلية. عبارات محورية: الزلزال، النوع الجنساني، باكستان ، التعافي، النساء 摘要: 本研究旨在了解在2005年10月克什米尔地震之后，在巴基斯坦控制的阿扎德克什米尔的琅迦普拉地区（Langarpura）的联合议会，妇女是如何参与恢复进程的。该研究开展了焦点组讨论（n=2）、半结构访谈（n=34）和参与者观察，总计48名参与者参加了研究。结果显示，琅迦普拉地区的妇女在繁衍后代、生产和社区领域扮演了各种重要的角色。妇女在其中扮演的角色，包括做饭、清洁和照顾牛群的常规家庭责任，此外，还包括非传统的责任，比如重建家园。琅迦普拉地区的妇女还扮演了生产领域的角色，包括参加创收活动，如搬运建筑材料和水，以赚取日薪，在田间工作，乳品业劳作，以及从事教育和卫生领域的工作。另一方面，妇女的社区角色包括搜索和救援活动，照顾伤员，集体做饭与共享食物，此外，还包括非传统角色，监督公共设施重建，包括学校、道路和供水设施，以及创办缝纫中心，为当地妇女提供职业培训。 关键词：地震、性别、巴基斯坦、恢复、妇女